2005
DOI: 10.1103/physrevb.72.155404
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and dissociation of hydrogen molecules on bare and functionalized carbon nanotubes

Abstract: We investigated interaction between hydrogen molecules and bare as well as functionalized singlewall carbon nanotubes (SWNT) using first-principles plane wave method. We found that the binding energy of the H2 physisorbed on the bare SWNT is very weak, and can be enhanced neither by increasing the curvature of the surface through radial deformation, nor by the coadsorption of Li atom that makes the semiconducting tube metallic. Though the bonding is strengthened upon adsorption directly to Li atom, yet its nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
188
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(212 citation statements)
references
References 34 publications
(28 reference statements)
21
188
1
2
Order By: Relevance
“…This difference in hydrogen adsorption can be attributed to the difference in the location of the metal dopant, that is, in the Ti-doped carbon nanotube, the Ti atom tends to occupy the hollow site of the carbon nanotube whereas in the Pt-doped BN nanotube the Pt atom favors the BA site. Indeed, it has been reported that for the Pt-doped carbon nanotube, 22 the first H 2 is actually adsorbed in the molecular form if the Pt atom occupies the bridge site of the carbon nanotube. On the other hand, we also obtained a locally stable configuration such that the adsorbed hydrogen is in the atomic form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in hydrogen adsorption can be attributed to the difference in the location of the metal dopant, that is, in the Ti-doped carbon nanotube, the Ti atom tends to occupy the hollow site of the carbon nanotube whereas in the Pt-doped BN nanotube the Pt atom favors the BA site. Indeed, it has been reported that for the Pt-doped carbon nanotube, 22 the first H 2 is actually adsorbed in the molecular form if the Pt atom occupies the bridge site of the carbon nanotube. On the other hand, we also obtained a locally stable configuration such that the adsorbed hydrogen is in the atomic form.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, hydrogen adsorption on metal-doped carbon nanotubes and fullerenes has been investigated. [19][20][21][22][23] The doping of SWCNT and fullerenes can generally promote more hydrogen uptake. The aim of this article is to assess to what extent the Pt-doped BN nanotubes can enhance the hydrogen uptake by using DFT methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel concept to overcome these obstacles has been suggested [7][8][9][10][11][12][13][14]. It was predicted that a single Ti atom affixed to carbon nanostructures, such as C 60 or nanotubes, strongly adsorbs up to four hydrogen molecules [7,8,10].…”
mentioning
confidence: 99%
“…There have been a great number of reports on the search for new routes to engineer nanomaterials so that (a) they dissociate H 2 molecules into H atoms and (b) reversibly adsorb hydrogen molecules at ambient conditions 1,2,3,4,5,6,7,8,9 . Much effort has been focused on the engineering of carbon-based materials such as nanotubes 10,11 and metal hydrides such as alanates 12 . It is found that while hydrogen-carbon interaction is too weak 10 , the metal-hydrogen interaction is too strong for hydrogen storage at ambient conditions.…”
mentioning
confidence: 99%
“…Much effort has been focused on the engineering of carbon-based materials such as nanotubes 10,11 and metal hydrides such as alanates 12 . It is found that while hydrogen-carbon interaction is too weak 10 , the metal-hydrogen interaction is too strong for hydrogen storage at ambient conditions. Very recently we have shown 13 a novel way to overcome this difficulty by forming artificial metal-carbide like structures on carbon singled-wall nanotubes (SWNT).…”
mentioning
confidence: 99%